Effect of Naira Devaluation on Nigeria’s Trade Balance With China - Gbadebo, Adedeji (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This study investigates the influence of the Naira devaluation on Nigeria's trade balance with China, with an emphasis on export-import dynamics and bilateral trade imbalances. The goal is to examine how currency depreciation affects trade volumes, structural vulnerabilities, and economic imbalances between the two countries. The study used an exploratory research approach, using secondary data from trade statistics, Central Bank of Nigeria publications, and foreign databases to identify patterns and causal relationships. Nigeria's trade imbalance with China has increased to 18 billion in 2023, owing to inelastic demand for Chinese commodities and reliance on USD-priced crude oil exports. While devaluation raised import costs and inflationary pressures (33% by early 2024), it did not considerably increase non-oil exports or reduce import reliance. Structural issues, such as insufficient industrial capacity and informal trading networks, exacerbated consequences. Furthermore, China's Belt and Road Initiative (BRI) initiatives exacerbated economic imbalances by emphasizing Chinese inputs and labor. The paper suggests expanding Nigeria's export base through agro-processing and light manufacturing, adopting import substitution programs, stabilizing foreign exchange regimes, renegotiating Chinese loan conditions, and negotiating advantageous trade agreements to reduce deficits. These steps seek to strengthen Nigeria's trade resilience and minimize reliance on China.